Enhancing MSME Capacity Through Product Innovation for Sustainable Community Empowerment - Fitri, Raisa; Nora, Elfia; Wiliandri, Ruly; Lia, Della Ayu Zonna; Sopiah; Ayu, Anastasia; Priandini, Donna Alexandra (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study addresses challenges faced by Bianana MSME in Malang, Indonesia, including stagnant product innovation and inefficient manual packaging, which hinder competitiveness. It aims to enhance MSME capacity through technological adoption and flavor innovation to support sustainable local economic development. Method: A community service approach was employed, involving problem identification, training, and evaluation. Data were collected via observation, interviews, and direct assessment, focusing on implementing continuous sealer technology and developing new flavor variants. Practical Applications: The use of continuous sealer machines improved packaging efficiency, extended shelf life from 2 to 4–5 weeks, reduced product damage to below 3%, and increased daily production by 35%. Product innovation training enabled the creation of market-responsive flavors, enhancing competitiveness and market reach. Conclusion: The integration of technology and innovation significantly improved product quality and business performance, demonstrating an effective model for sustainable MSME development and community empowerment.